Rhodococcus erythropolis DCL14 Contains a Novel Degradation Pathway for Limonene - van der Werf, Mariët J. (American Society for Microbiology, 1999)
Strain DCL14, which is able to grow on limonene as a sole source of carbon and energy, was isolated from a freshwater sediment sample. This organism was identified as a strain of Rhodococcus erythropolis by chemotaxonomic and genetic studies. R. erythropolis DCL14 also assimilated the terpenes limonene-1,2-epoxide, limonene-1,2-diol, carveol, carvone, and (−)-menthol, while perillyl alcohol was not utilized as a carbon and energy source. Induction tests with cells grown on limonene revealed that the oxygen consumption rates with limonene-1,2-epoxide, limonene-1,2-diol, 1-hydroxy-2-oxolimonene, and carveol were high. Limonene-induced cells of R. erythropolis DCL14 contained the following four novel enzymatic activities involved in the limonene degradation pathway of this microorganism: a flavin adenine dinucleotide- and NADH-dependent limonene 1,2-monooxygenase activity, a cofactor-independent limonene-1,2-epoxide hydrolase activity, a dichlorophenolindophenol-dependent limonene-1,2-diol dehydrogenase activity, and an NADPH-dependent 1-hydroxy-2-oxolimonene 1,2-monooxygenase activity. Product accumulation studies showed that (1S,2S,4R)-limonene-1,2-diol, (1S,4R)-1-hydroxy-2-oxolimonene, and (3R)-3-isopropenyl-6-oxoheptanoate were intermediates in the (4R)-limonene degradation pathway. The opposite enantiomers [(1R,2R,4S)-limonene-1,2-diol, (1R,4S)-1-hydroxy-2-oxolimonene, and (3S)-3-isopropenyl-6-oxoheptanoate] were found in the (4S)-limonene degradation pathway, while accumulation of (1R,2S,4S)-limonene-1,2-diol from (4S)-limonene was also observed. These results show that R. erythropolis DCL14 metabolizes both enantiomers of limonene via a novel degradation pathway that starts with epoxidation at the 1,2 double bond forming limonene-1,2-epoxide. This epoxide is subsequently converted to limonene-1,2-diol, 1-hydroxy-2-oxolimonene, and 7-hydroxy-4-isopropenyl-7-methyl-2-oxo-oxepanone. This lactone spontaneously rearranges to form 3-isopropenyl-6-oxoheptanoate. In the presence of coenzyme A and ATP this acid is converted further, and this finding, together with the high levels of isocitrate lyase activity in extracts of limonene-grown cells, suggests that further degradation takes place via the β-oxidation pathway.